Dual cutaneous lymphoid dyscrasias in a pediatric patient, with progression to mycosis fungoides: case report - Cortez-Vila, Jorge A.; Lacy-Niebla , Rosa M. (International Journal of Contemporary Pediatrics, 2024)
This case report explores the progression of cutaneous lymphoid dyscrasia to a lymphoma in a 13-year-old boy with pityriasis lichenoides chronica and lichenoid pigmented purpuric dermatitis, the latter evolving into mycosis fungoides. We highlight some of the crucial clinical and histological characteristics to differentiate between these entities. Early identification of this progression is critical not only for preventing further lymphoma development but also for initiating prompt therapy.